2017
DOI: 10.1016/j.physbeh.2016.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stressors and young adolescents' depressive symptoms: Does high vagal suppression offer protection?

Abstract: Grounded in a dual-risk, biosocial perspective of developmental psychopathology, this study examined the role of higher vagal suppression in providing young adolescents protection from four parenting stressors. It was expected that lower vagal suppression would increase youth vulnerability to the deleterious effects of these parenting stressors. Depressive symptoms were examined as a central marker of socioemotional difficulties during early adolescence. The four parenting stressors examined were interparental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
1
13
0
1
Order By: Relevance
“…Finally, it is also worth noting that although our findings concerning RSAR replicate similar findings in the literature (see Hamilton & Alloy, ), others have found that RSAR indexes internalizing symptoms uniquely in boys, but not girls (Fletcher et al, ; Nederhof et al, ). One possible reason for these different findings concerns the nature of the tasks used across studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, it is also worth noting that although our findings concerning RSAR replicate similar findings in the literature (see Hamilton & Alloy, ), others have found that RSAR indexes internalizing symptoms uniquely in boys, but not girls (Fletcher et al, ; Nederhof et al, ). One possible reason for these different findings concerns the nature of the tasks used across studies.…”
Section: Discussionsupporting
confidence: 91%
“…One possible reason for these different findings concerns the nature of the tasks used across studies. Both Fletcher et al () and Nederhof et al (), utilized a social stress task, designed to elicit performance‐related social stress. This is distinct from the current study, which elicited a stress response related to interpersonal problem‐solving with a parent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical ideas of modern researchers base on ideas of Z. Freud and A. Freud [14,15]. The representatives of this direction regarded psychological protection as the mean of solution the conflict between conscious and unconscious [12,13,16,18]. By opinion of some scientists [6, 7, 10 19], the most constructive psychological protection kinds are compensation and rationalization.…”
Section: Introductionmentioning
confidence: 99%